2005
DOI: 10.1021/jo051949c
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Bowl-Shaped Hydrocarbons:  Dianions and Tetraanions of Annelated Corannulenes

Abstract: [structure: see text] The reduction of several annelated corannulene derivatives was undertaken using lithium and potassium metals. It was found that annelation affects the annulenic character of corannulene by changing its charge distribution; the dianions of derivatives that are annelated with six-membered rings have less annulenic character and are less paratropic than corannulene dianion. This effect is even more pronounced in corannulenes that are peri-annelated with five-membered rings. The alkali metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…The highly enantioselective direct conjugate addition of ketones to nitroalkenes has been promoted by a chiral primary amine-thiourea catalyst (7). 31 The observed anti diastereoselectivity has suggested participation of a (Z)-enamine intermediate, given de the complementary diastereoselectivity obtained in analogous reactions involving (E)enamines generated from secondary amine catalysts.…”
Section: Eementioning
confidence: 99%
See 2 more Smart Citations
“…The highly enantioselective direct conjugate addition of ketones to nitroalkenes has been promoted by a chiral primary amine-thiourea catalyst (7). 31 The observed anti diastereoselectivity has suggested participation of a (Z)-enamine intermediate, given de the complementary diastereoselectivity obtained in analogous reactions involving (E)enamines generated from secondary amine catalysts.…”
Section: Eementioning
confidence: 99%
“…66 By measuring the rates of loss of chlorobenzene in the varied media and also by certain 7 Li NMR studies, a gradual, controlled increase in the basicity of n-BuLi in cyclohexane with increasing increments of THF or TMEDA has been observed.…”
Section: Organometallic Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…1), unequivocally shows that 6-8 possess markedly more positive AEAs (Table 2). Hence, 6-8 are inherently better electron acceptors then 9 (see also [30]). Interestingly, the AEAs of 3 and 5-8 (Table 2), which are surface sub-structures of C 60 and C 70 , correspond to Ca.…”
Section: åàmentioning
confidence: 99%
“…26 In particular, it has been suggested that alkali- 1 complexes of the type X 4 C 20 H 10 (X ≠ Li) will not form sandwich structures with four alkali ions located between two bowl molecules, as was the case for Li 4 - 1 . 27 Until recently, 28 compounds containing anions of 1 were exclusively characterized in solution, and there only the tetraanionic Li- 1 aggregate has been identified. 29 Such tetraanionic Li- 1 motif has also been used to create supramolecular architectures with bicorannulenyl.…”
Section: Introductionmentioning
confidence: 99%